Contribution of International Organizations to the Development of Education in Nigeria - Ogunode, Niyi Jacob; Evans Oluwagbamila Ayeni; Joshua Ogwuche (PT FORMOSA CENDEKIA GLOBAL, 2023)
The paper examined the contributions of international organizations towards the development of education in Nigeria. The paper used role theory to provide a theoretical framework. Documentary research method was adopted for the study, hence secondary data were consulted. The secondary data were sourced from online publications and print materials. Content analysis was used to select the suitable literature for the study. The paper identified funding, infrastructural facilities development, provision of learning and teaching resources, provision of technical support for educational planning, policy formulation and educational management, provision of capacity building programmes and implementation of projects or programmes meant to increase access to education services as contributions of international organisations to education. Based on these findings, the paper recommended that the federal government should establish an agency to coordinate the activities of all international organizations operating in Nigeria to improve their effectiveness. International organizations that are programmes inclined to education should always be involved and included in programmes concerning educational management. International organizations should be encouraged to participate in the development of education in Nigeria.